Pengembangan Keterampilan Berfikir Kritis Mahasiswa yang Memiliki Gaya Belajar Berbeda Melalui Penerapan Metode Debat - Ninies Er yadini; Durrotun Nafisah (Journal An-Nafs: Kajian Penelitian Psikologi, 2017)
This study aims to develop students' critical thinking skills using the method of debate in terms of student learning styles. This research was conducted on 58 students of STKIP PGRI Lamongan who take social science education course. The technique of collecting data using questionnaires and tests the ability to think critically. Analysis using descriptive analysis and ANOVA two lanes by using parametric statistical methods, parametric statistics. This is done because it is based on a statistical test, normal research data distribution and homogeneous. The subjects of the study were 58 students drawn from two classes that had the same relative ability. This is based on the calculation of pretest value using t test (t-test) obtained the result that t arithmetic = 0.537 <t table = 1.955 at a significant level of 0.471> 0.05, meaning there is no significant difference pretest value of students' critical thinking skills between groups the experimental class student with the control class student group before being given treatment. The result of posttest data analysis shows that the average of critical thinking skill of student group that is discussed by debate method is 41.43 with standard deviation of 7.045. Based on the analysis results can be known 1) there is a significant difference in students' critical thinking skills between those taught by the method of debate (experimental class) with those taught by the lecture method (control class). It is based on a F value of 33,577 with a probability of 0.000. Based on the analysis results can be seen that there are differences in critical thinking skills between who have visual learning style, auditory and kinestetik. the second result shows that there is no interaction of learning method with learning style to students' critical thinking skill. It is based on F arithmetic 0,599 with probability 0,553.